Analisis ‘Illah Hukum Terhadap Hadis Perubatan Nabawī Berkaitan Habbatussauda, Madu, Susu Berserta Air Kencing Unta - Ahmad Akram Mahmad Robbi; Mohamad Faiq Mohamad Sharin; Irwan Mohd Subri (USIM Press, 2024)
Indexed by MyCite